Accounting tools and tax optimization schemes - Tuchak, Tetiana (Management and Entrepreneurship: Trends of Development, 2019)
The evolution of taxes and the increasing role of public financial resources in the life of modern society have contributed to the transformation of taxation into an important, complex, specific area of activity with their own laws of development. First of all, these include the classical principles of taxation – equality, neutrality, convenience, simplicity, etc. Last but not least, the principle of non-taxation takes place in this list. Since the state’s existence is not limited by any calendar, let alone tax terms, the state still has a constant need for tax revenues and is obliged to take into account the need to renew its financial resources in the future, recognizing that this is real only if there is normal production. By re-taxing the economy today, the state is depriving itself of future revenues with all the ensuing consequences. Therefore, a competent definition of the boundaries of the tax burden involves the development of production and ensuring conditions for the growth of tax revenues. Oppressing the economy, suppressing the taxpayer, the tax destroys its own foundation and itself. The ongoing reformation of the tax system as a whole today in the conditions of the modern Ukrainian economy is the desire of the state systems to determine the optimum limits of the tax burden, which can satisfy the financial interests of the state and not break the delicate fragile balance of social and economic conditions of modern society. The aim of research is determining the features of tax planning formation for tax optimization purposes and to improve the economic management system at the enterprise through the use of special optimization schemes and the use of accounting tools. Methodology: the theoretical justification is based on observations, groupings, analytical work in determining the organization of tax planning. Methodological and general scientific principles of complex researches became the theoretical basis. The scientific importance of the work lies in the fact that results is the systematization of theoretical and practical provisions of tax optimization of the enterprise. The value of the research is that the materials of the conducted research will be useful for further study of the specifics of tax optimization at enterprises. JEL Classification: H20, H21, H22, H26, H30.